Factors Affecting Students’ Willingness to Speak English at Eleventh Grade of SMA Pertiwi Medan - Aisyah Febrianti; Marisi Debora (Universitas Negeri Medan, 2023)
This study is about Factors Affecting Students’ Willingness to Speak English at Eleventh Grade of SMA Pertiwi Medan. The aim of this study is to find out the factors that affect students’ willingness to speak English at eleventh grade students of SMA Pertiwi Medan. The data of this study was taken from eleventh grade students in SMA Pertiwi Medan. The research design of this data was qualitative research design. The data were collected by observation and interview. The result of the study revealed that there were individual and situational factors that affect students’ willingness to speak. They were self-confidence, perceived speaking ability, learning anxiety, motivation and personality as the individual factors. The situational factors consisted of effect of task type, topic, interlocutor, teacher and classroom atmosphere.Keywords: Willingness to speak, English, Senior High School